A Review on Anti-Stress Activity of Piper Methysticum - Sharma, Ankit; Anchariya, Rahul; Dubey, Chetan (Asian Journal of Pharmaceutical Research and Development, 2020)
On the basis of study conducted on the plant Piper methysticum G. (Forst), Piperaceae, it was found that Kava has storage of active constituents present in its roots and rhizomes. Traditionally its root part is used to relax body and mind and promote restful sleep, therefore it is necessary to explore its importance as excellent nervine herb. Literature survey revealed that kavalactones are responsible for biological activity which include local anaesthetic, antispasmodic, Musculo-relaxant, antimycotic, sedative, anticonvulsive, analgesic, antianxiety and neuroprotective effects etc. which proves it has potent psychoactive ability but, the claim of therapeutic efficacy of the plant as an anti-stress or adaptogen yet has not been scientifically scrutinized. However, synthetic drugs are widely prescribed to reduce stress and stress induced symptoms but their soporific effect, risk of dependence and withdrawal effects limits their long-term use. Based on clinical studies Kava shows its efficacy within one week at moderate dose. Evidently, the herbal formulations claimed to enhance physical endurance; mental functions and non-specific resistance to withstand stress without altering the physiological functions of the body hence, it is essential to study its safety and efficacy for its therapeutic use.